Student’ Perception of the Use Artificial Intelligence (AI) Technology in Student Creativity Completing Academic Tasks - Putri Mariyanti; Tri Nur Wahyudi (Didaktika: Jurnal Kependidikan, 2025)
In the digital era Artificial Intelligence (AI) can help complete work quickly, especially in the academic field used by students. The purpose of this study is to determine students perceptions and the usefulness of using AI in helping to complete academic tasks. The object of this research is at Universitas Muhammadiyah Surakarta, while the subjects are UMS students. The method in this research is to use mixed method with sequential exploratory approach, the data collection techniques used observation, interviews, documentation (qualitative), and questionnaires (quantitative). The number of informants was 12 students (qualitative), and 157 respondents (quantitative). The results of this study show that the perception of the use of AI is needed to help students complete academic tasks including : articles, proposals, practice reports, citations and bibliographies, transating, making presentation. While the types of AI that are often used by students are ChatGPT, Google Scholar, Canva, Perplexity, Mendeley, Grammarly, Google Gemini, Poe AI, Blackbox AI, and Cici AI. For the usefulness of AI 56,7% for working on articles, 50,3% for working on papers or essays, 33,1% for working on proposals, 32,5% for working on final reports, 26,8% for working on presentations, 26,1% for writing, 0,6% for other tasks.